Territorialidade e agricultura: Percepções na rizicultura familiar no município de gaspar - SC, BRASIL - Schneider, Lindair Maria Lanz; Mantovaneli, Oklinger [UNESP]; Pellin, Valdinho (My University, 2015)
The study explores themes of livelihood in agriculture and territory in the permanence and transformation processes of crop. A rice cultivation analysis was conducted since the 70's until 2008, covering a new observation in August 2013 in the Municipality of Gaspar - SC. This analysis considered, cultural, political and economic identities, as well as the connection of that population with the agricultural territory. Also, it was performed with the use of triangulation techniques and content analysis. As results stand out the loss of the importance of the family institution, breaking of the agriculture charming by the contemporary generations and an offset under the territorial perspective.
Territoriality and agriculture: Perceptions in the family rice cultivation in the municipality of gaspar - SC, BRAZIL
Keywords: Familiar agriculture; Rice cultivation; Rural development; Territory